Dakwah Kyai Kampung - Wigati, Yunika Indah; Khayati, Khamali (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
Da'wah is something that cannot be separated from Muslims. Every Muslim has an obligation to take part in Islamic da'wah. Da'wah is not limited to age, time, place, or culture in society. This study will discuss the da'wah carried out by one of the Da'i in the Pekalongan area, precisely in Pucung village, Tirto sub-district. Kyai Kampung is the term for a Da'i who comes from a village and preaches in it. The discussion in this study includes how da'wah is carried out, such as the form of da'wah, da'wah methods, and media in da'wah. This study uses a phenomenological approach to see how da'wah occurs in the Pucung village community.